The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.pocean.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The importance of sub-mesoscale processes for the exchange of properties through the Strait of Gibraltar

Abstract: This article presents a detailed analysis of the sub-mesoscale transport processes in the Strait of Gibraltar. The interest is focussed on the Camarinal Sill region, and special attention is paid to the across-strait transport processes, the divergences and convergences in the central zone, and the small-scale circulation patterns along the northern coastal margin. The analysis is based on high-resolution (7 m) SST images acquired by an airborne hyper-spectral scanner, and has been complemented with a rhodamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 19 publications
(24 reference statements)
1
15
0
Order By: Relevance
“…Bruno et al, 2002;García-Lafuente et al, 2002) and could be easily identified by remote sensing as a strong cooling of surface waters (e.g. Bruno et al, 2013). Our model, even if correctly reproducing the mean fluxes through the Strait (Peliz et al, 2013b), is lacking these cyclic, recurrent mixing processes and, hence, simulates warmer than observed SST.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Bruno et al, 2002;García-Lafuente et al, 2002) and could be easily identified by remote sensing as a strong cooling of surface waters (e.g. Bruno et al, 2013). Our model, even if correctly reproducing the mean fluxes through the Strait (Peliz et al, 2013b), is lacking these cyclic, recurrent mixing processes and, hence, simulates warmer than observed SST.…”
mentioning
confidence: 71%
“…Sarhan et al, 2000;Macias et al, 2008aMacias et al, , 2009 or the Strait of Gibraltar (e.g. Macias et al, 2008b;Bruno et al, 2013;Ramirez-Romero et al, 2014) are much more common.…”
Section: Introductionmentioning
confidence: 99%
“…Cape Trafalgar is assumed to act as a source of biomass exporting chlorophyll and nutrient rich waters towards the Alborán Sea. Sub-mesoscale processes have been identified as important mechanisms in the chlorophyll distribution between coastal zones and the main channel of the SoG [19,52], along with the transport of nutrients to the Mediterranean Sea [14], highlighting mainly the role of the fortnightly tidal cycle [12,47]. A lateral advection of coastal waters into the centre of the channel takes place when internal waves are generated over the Camarinal Sill (Figure 1a) during the spring tides [12,52], and also, although it is less evident, during the release of arrested internal waves during neap tides [47].…”
Section: Discussionmentioning
confidence: 99%
“…As evaporation exceeds the sum of precipitation and river discharge [8], there is a two-layer inverse estuarine circulation that results in an upper Atlantic layer flowing towards the Alborán Sea and an outflow of deep high-density Mediterranean waters towards the Atlantic Ocean [9]. However, this general scheme increases its complexity due to a variety of phenomena such as intense and frequent wind (e.g., [10,11]), transport fluctuations due to the tidal cycles (e.g., [4,12]), or the generation of high-amplitude internal waves associated with periods of spring and neap tides (e.g., [13,14]). Furthermore, the topography strongly modifies this intricate scheme, and is particularly noticeable at the tidal scale (e.g., [15]).…”
Section: Introductionmentioning
confidence: 99%
“…The generation of internal waves in the Camarinal Sill causes the suction of coastal waters rich in chlorophyll towards the centre of the channel Navarro et al, 2011;Vázquez et al, 2009) and enhances the upwelling of deep nutrient-rich waters in the same region (Echevarría et al, 2002). The coupling of both processes favours the phytoplankton growth during its advection to the Alboran Sea (Bruno et al, 2013) and would support the spread by the AJ as the origin of population cell density observed in mesoscale patches in the NWAF.…”
Section: The Northwestern Alboran Frontmentioning
confidence: 94%